THE IMPACT OF TIME MANAGEMENT ON ADMINISTRATIVE CREATIVITY IN LIGHT OF A SAMPLE OF IRAQI ORGANIZATIONS. MODEL MEDICINE CITY HOSPITAL - Inam Abass Hamidi (Scholar Express Journals, 2023)
There is a group of works that the administration seeks to implement and it must deal with time effectively and successfully, as this is a basic indicator for it in how to measure its effectiveness in organizing time, investing it and distributing it to the various tasks effectively to achieve the goals it adopts by directing the behavior to accomplish the tasks in the specified time and in the appropriate manner without wasting and wasting time . The problem can be summed up in the fact that the contemporary conditions in which organizations live require management to work creatively and with different thinking with each event that includes a problem that must be dealt with and find the appropriate solution for it in record time and without committing a new mistake that will lead to the accumulation of work, increase in problems and loss of time. The research hypothesis is that there is an effect of time management on administrative creativity in the medical city in Baghdad
Keywords: problems; medical; loss; hypothesis